Revisiting the recent California drought as an extreme value. Issue 16 (22nd August 2015) - Robeson, Scott M.
Abstract: Spatially weighted averages of Palmer Drought Severity Index (PDSI) over central and southern California show that the 1 year 2014 drought was not as severe as previously reported, but it still is the most severe in the 1895–2014 instrumental record. Using the typical adjustment procedure that matches the mean and standard deviation of tree ring PDSI values to those of instrumental data shows over 10 droughts from 800 to 2006 that were more severe than the 1 year 2014 drought, with the 2014 drought having a return period of 140–180 years. Quantile mapping allows for a closer correspondence between instrumental and tree ring PDSI probability distributions and produces return periods of 700–900 years for the 1 year 2014 drought. Associated cumulative 3 and 4 year droughts, however, are estimated to be much more severe. The 2012–2014 drought is nearly a 10, 000 year event, while the 2012–2015 drought has an almost incalculable return period and is completely without precedent. Key Points: The 1 year 2014 California drought was a multicentury‐scale event The cumulative 2012–2014 California drought was a multimillennial‐scale event The relative severity of the cumulative 2012–2015 drought is unprecedented